Prediction and Identification of Antioxidant Peptides in Potato Protein Hydrolysate - Juan Wu; Chao Mao; Wenli Zhang; Yu Cheng (Journal of Food Quality)
Principal component analysis (PCA) was used to cluster the possible amino acid compositions of antioxidant peptides in potato protein hydrolysate (PPH). The antioxidant peptides exhibiting high ABTS+• scavenging capacity were isolated with the procedure of ultrafiltration, gel filtration, and preparative RP-HPLC and identified by UPLC-MS/MS. Phe, Tyr, and His were shown to group together with ABTS+• scavenging capacity in component matrix plot. Three prominent peptides, namely, Phe-Tyr, Tyr-Phe-Glu, and Pro-Pro-His-Tyr-Phe, which matched the sequence of patatin and were made up of Phe and Tyr, were identified. The peptide Tyr-Phe-Glu demonstrated antioxidant activity against Caco-2 cell oxidation induced by H2O2. The results suggested that multivariate analysis could be used to predict the amino acid compositions of antioxidant peptides.